If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -36 = -11n + 8n Combine like terms: -11n + 8n = -3n -36 = -3n Solving -36 = -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. -36 + 3n = -3n + 3n Combine like terms: -3n + 3n = 0 -36 + 3n = 0 Add '36' to each side of the equation. -36 + 36 + 3n = 0 + 36 Combine like terms: -36 + 36 = 0 0 + 3n = 0 + 36 3n = 0 + 36 Combine like terms: 0 + 36 = 36 3n = 36 Divide each side by '3'. n = 12 Simplifying n = 12
| 6y-60=42 | | 12=x-(-11) | | -36=k-13+14k | | 13p+6=32 | | sin^-1(3.2/4) | | 34=x+9+12 | | 11m+8=19 | | 0.3x-0.6=0.2x+7 | | -n-7=-16 | | 0=-13b+13b | | 9y^4+12y^2+1=0 | | -13z+13=26 | | -3(4n+6)=-6(n-8) | | .03x+.05(200-x)=9 | | 7m-25=-4 | | 2m+20=26 | | X^2-8x-4=-11 | | 3.3=1.5-0.4 | | x+4k=0 | | -18=x-5 | | -15x+25=-95 | | 9z-17=-35 | | 10y-2=48 | | -11y-9=-86 | | -15p-1=-46 | | 31-3n=4(n+6) | | C+32=-8 | | (5x^3+1)-1=0 | | 3822/14 | | 60.00+42.95p=25.00+49.95p | | -4y-13=15 | | 10x-11=-1 |